Analisis Kesalahan Penggunaan Huruf Kapital pada Poster Edukatif Siswa Sekolah Dasar: Studi Kasus di SDN Tanggultlare (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze errors in the use of capital letters in educational poster media made by grade VI students of SDN Tanggultlare. Posters are a form of visual literacy used in learning to foster creativity and students' writing skills. The research method uses a qualitative descriptive approach with documentation and content analysis techniques. Data were taken from seven posters resulting from the Indonesian Language subject project. The results showed that there were 22 capitalization errors, including errors in writing capital letters at the beginning of sentences, proper names, place names, and the influence of digital-style writing such as 'By:' and artistic lowercase letters. These results indicate the importance of integrating PUEBI materials into visual literacy practices in elementary schools.